EPIDEMIOLOGY OF THE PEDIATRIC EYE INJURIES IN THE SUGHD REGION OF TAJIKISTAN - KH.J. KARIM-ZADE; N.A. OCHILZODA; Z.A. DADОBOEV (Паёми Сино, 2020)
Objective: To study epidemiology and clinical features of of eye injuries in children in Sughd Region of the Republic of Tajikistan from 1993 up to 2013.